2005
DOI: 10.2519/jospt.2005.35.9.572
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Correlates of Physicians' Referral Diagnoses for Physical Therapy

Abstract: Study Design: Randomized multicenter retrospective chart review of medical referral diagnoses and corresponding referral, patient, and physician demographic data. Objective: To examine the information content of medical referral diagnoses provided to outpatient physical therapists with respect to physician and patient characteristics. Background: Previous studies indicate that physicians commonly provide nonspecific referral diagnoses to physical therapists. The effects of patient and physician characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
0
14
0
1
Order By: Relevance
“…A recent investigation of referral diagnoses did reveal an association between specialist physicians and specificity of diagnoses included in referrals to physical therapy. 10 In the current study, patients treated in the spine center were more likely to be referred by specialist physicians (analysis not shown), which may help to explain the association between spine center and referral status.…”
Section: Subjectsmentioning
confidence: 87%
See 1 more Smart Citation
“…A recent investigation of referral diagnoses did reveal an association between specialist physicians and specificity of diagnoses included in referrals to physical therapy. 10 In the current study, patients treated in the spine center were more likely to be referred by specialist physicians (analysis not shown), which may help to explain the association between spine center and referral status.…”
Section: Subjectsmentioning
confidence: 87%
“…A more recent investigation of diagnosis specific referrals reported that approximately 68% of diagnoses were nonspecific and required a physical therapist to perform a differential diagnosis. 10 A study of referrals in the 1980s in Australia suggested an evolution toward more open referrals to physical therapy. 30 Other authors have noted the paucity of research on the impact of referral patterns on health outcomes, and have called for an increase in focus on this area.…”
Section: Subjectsmentioning
confidence: 99%
“…A study of patients being referred to physical therapy by a sample of general practitioners and specialists showed that less than one third of referrals included a specific diagnosis. 9 Therefore, PTs must use clinical judgment to determine the etiology of the symptoms in order to provide treatment more than may be commonly recognized. 10 Zero adverse events were seen in a large retrospective study of open access to patient care in a multi-center military setting.…”
mentioning
confidence: 99%
“…1 The same study illustrated that physical therapists must assume a greater diagnostic role and must routinely provide medical screening and differential diagnosis of pathology during the examination. 1 Similarly, studies conducted in Australia and Canada have concluded that the majority of referrals for physical therapy are not provided with a specific diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…1 The same study illustrated that physical therapists must assume a greater diagnostic role and must routinely provide medical screening and differential diagnosis of pathology during the examination. 1 Similarly, studies conducted in Australia and Canada have concluded that the majority of referrals for physical therapy are not provided with a specific diagnosis. 2,3 Medical screening is important, since physical therapists are increasingly functioning as the primary contact for patients with neuromusculoskeletal dysfunctions, 4,5 which means a greater likelihood of encountering patients with non-musculoskeletal disorders, including psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%